Food Waste Generation: A Case Study in Taman Pura Kencana and Taman Universiti - Ahmad Sabli, Siti Nursyaidatul Azwah; Zainun, Noor Yasmin (Recent Trends in Civil Engineering and Built Environment, 2023)
Food waste generation has become an unbearable issue faced by the world. Food waste consists of two classifications, which are food that was edible before it was thrown and food that was inedible before it was thrown. The aim of this study is to identify food waste generation in Taman Pura Kencana and Taman Universiti. Besides, this study also aiming on establishing food waste composition in Taman Pura Kencana and Taman Universiti. The flow of this case study begins with literature review based on previous studies to gain information needed in this study. Then the sample size of population in Taman Pura Kencana and Taman Universiti is determined by Raosoft Sample Size Calculator. In order to quantify food waste generation by the community, briefing on the procedure must be done to ensure the community understands the process well. Followed by making time arrangement with the community. The last procedure will be weighing the food waste generation and data collection. For food waste composition analysis, the procedure began with sampling food waste. The next procedure was sorting food waste into few categories. Weighing each food category comes next and lastly the data has been recorded. Based on the result, total food waste generation by community in Taman Pura Kencana and Taman Universiti were 1206.59 kg and 445.63 kg respectively. For food waste composition, there were seven food categories which are vegetables and fruits, meat, fishes and bones, eggshells, pastries, noodles, chips and others. The highest composition was others category which consist of rice, poor-shaped food and non-food. As a conclusion, the community in Taman Pura Kencana generated more food waste than community in Taman Universiti and the most common type of food waste composition is rice. From the study, it is intended that this case study can contribute in reducing food waste generation in the future.